Comparison between outcome of Inside-out & Outside-in mastoidectomy (Bangladesh Journal of Otorhinolaryngology, 2020)
Background: Chronic suppurative otitis media is a disease that is known worldwide and that is more common in developing countries. Many techniques are available for operating the disease.Objectives: To compare outcome between Inside-out & Outside-in mastoidectomy.Methods: A cross-sectional study was conducted to compare outcome between Inside-Out & Outside-in mastoidectomy. Period of study was from July’ 2010 to March, 2012 in the Department of Otolaryngology and Head-Neck Surgery, BSMMU- DhakaResult: majority of the patient were found dry mastoid cavity 13(68.42%) and rest were wet mastoid cavity 6 (31.58%).On the other hand in outside–in mastoidectomy dry mastoid cavity were 80.6% and wet were 19.4%. In inside-out mastoidectomy, among 8 attic cholesteatoma cases 5(62.50%) had gained hearing (average 6.66 dB) and 3(37.50%) had no gain or loss of hearing (average 3.89dB); among 11 entire mastoid bowl cholesteatoma cases 3(27.27%) had gained of hearing (average 6.11dB) and 8(72.73%) had no gain or loss of hearing (average 6.87dB)Bangladesh J Otorhinolaryngol; April 2018; 24(1): 29-36